2012
DOI: 10.3109/13561820.2011.636157
|View full text |Cite
|
Sign up to set email alerts
|

From the nurses' station to the health team hub: How can design promote interprofessional collaboration?

Abstract: Interprofessional practice implies that health professionals are able to contribute patient care in a collaborative environment. In this paper, it is argued that in a hospital the nurses' station is a form of symbolic power. The term could be reframed as a "health team hub," which fosters a place for communication and interprofessional working. Studies have found that design of the Nurses' Station can impact on the walking distance of hospital staff, privacy for patients and staff, jeopardize patient confident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…Another study found that communication barriers between health professionals were related to poor design, lack of space, frequent interruptions, and a lack of privacy. Thus, this study highlighted the importance of a conducive workplace design in promoting IPC (Gum, Prideaux, Sweet, & Greenhill, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Another study found that communication barriers between health professionals were related to poor design, lack of space, frequent interruptions, and a lack of privacy. Thus, this study highlighted the importance of a conducive workplace design in promoting IPC (Gum, Prideaux, Sweet, & Greenhill, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…In 5 of the 11 studies (Gum et al, 2012;Hjalmarson et al, 2013;Kislov et al, 2012;Oandasan et al, 2009;Quinlan, 2009) it was possible to ascertain that observation data was initially collected independently from other data, and that the initial analysis stemmed from the observation data.…”
Section: Analysis Of Study Methodsmentioning
confidence: 99%
“…Within this category -opportunities for informal communication -sub categories included space and time, shared communication methods. Issues of both space and time emerged as key facilitators (or barriers) to communication (Bunniss and Kelly, 2008;Gum et al, 2012;Oandasan et al, 2009). Not only was the amount of shared physical work space identified as important, but so was the configuration of that space.…”
Section: Top Down Organisationmentioning
confidence: 97%
See 2 more Smart Citations